Regional conformational flexibility couples substrate specificity and scissile phosphate diester selectivity in human flap endonuclease 1. Issue 11 (30th April 2018) - Bennet, Ian A; Finger, L David; Baxter, Nicola J; Ambrose, Benjamin; Hounslow, Andrea M; Thompson, Mark J; Exell, Jack C; Shahari, Nur Nazihah B Md; Craggs, Timothy D; Waltho, Jonathan P; Grasby, Jane A
Abstract: Human flap endonuclease-1 (hFEN1) catalyzes the divalent metal ion-dependent removal of single-stranded DNA protrusions known as flaps during DNA replication and repair. Substrate selectivity involves passage of the 5′-terminus/flap through the arch and recognition of a single nucleotide 3′-flap by the α2–α3 loop. Using NMR spectroscopy, we show that the solution conformation of free and DNA-bound hFEN1 are consistent with crystal structures; however, parts of the arch region and α2–α3 loop are disordered without substrate. Disorder within the arch explains how 5′-flaps can pass under it. NMR and single-molecule FRET data show a shift in the conformational ensemble in the arch and loop region upon addition of DNA. Furthermore, the addition of divalent metal ions to the active site of the hFEN1–DNA substrate complex demonstrates that active site changes are propagated via DNA-mediated allostery to regions key to substrate differentiation. The hFEN1–DNA complex also shows evidence of millisecond timescale motions in the arch region that may be required for DNA to enter the active site. Thus, hFEN1 regional conformational flexibility spanning a range of dynamic timescales is crucial to reach the catalytically relevant ensemble.